A rare new species of Lento Evans, 1955 (Lepidoptera: Hesperiidae) from the western Amazon Basin - Adalberto Dantas de Medeiros; Olaf Hermann Hendrik Mielke (Papéis Avulsos de Zoologia)
Abstract A rare new species of skipper butterfly from the western Amazon Basin (Cuzco and Madre de Dios, Peru and Acre, Brazil) belonging to the subtribe Moncina (Lepidoptera: Hesperiidae) is herein described: Lento yaguar Medeiros & O. Mielke sp. nov. The new species can be easily recognized by the conspicuous yellow and black hind wing ventral pattern, that resembles the peculiar color of a jaguar’s skin. This interesting pattern is unique among Hesperiidae, and a similar pattern occurs only in a few species of Riodinidae. The presence of an unusual, modified scale patch on the male abdominal tergites III, IV, and V of L. yaguar sp. nov., is herein hypothesized as an androconial organ and represents the first record of this kind of structure on the abdominal tergum of a skipper species.